The Role of Iron in Cancer Progression - Guo, Qianqian; Li, Liwen; Hou, Shanshan; Yuan, Ziqiao; Li, Chenhui; Zhang, Wenzhou; Zheng, Lufeng; Li, Xiaoman (Frontiers in Oncology, 2021)
Iron is an essential trace element for the human body, and its deficiency or excess can induce a variety of biological processes. Plenty of evidences have shown that iron metabolism is closely related to the occurrence and development of tumors. In addition, iron plays an important role in cell death, which is very important for the development of potential strategies for tumor treatment. Here, we reviewed the latest research about iron metabolism disorders in various types of tumors, the functions and properties of iron in ferroptosis and ferritinophagy, and new opportunities for iron-based on treatment methods for tumors, providing more information regarding the prevention and treatment of tumors.